Effects of traditional Chinese exercises on post-stroke depression: a meta-analysis of randomized controlled trials - Li, Yan; Li, Xiaomei; Huang, Jingwen; Cai, Hejia (Frontiers in Public Health, 2025)
Post-stroke depression (PSD) is a common complication that worsens neurological recovery and increases mortality among stroke survivors, creating a significant burden on patients and families. While exercise interventions are known to alleviate depressive symptoms in mild stroke cases, the effects of traditional Chinese exercises on PSD have not been systematically reviewed. This study aimed to evaluate the clinical efficacy of traditional Chinese exercises in treating PSD. A comprehensive search of eight Chinese and English databases identified randomized controlled trials (RCTs) published up to July 2024. Data were independently screened, extracted, and analyzed using RevMan 5.3 and Stata 17, with heterogeneity assessed through sensitivity, subgroup, and meta-regression analyses. Ten RCTs involving 627 participants were included. Meta-analysis revealed that traditional Chinese exercises significantly reduced depressive symptoms and improved daily living abilities in PSD patients. Specifically, HAMD scores decreased [SMD = −1.40, 95% CI (−1.88, −0.92), p < 0.00001], treatment efficacy improved [OR = 3.74, 95% CI (1.69, 8.28), p = 0.001], FMA scores increased [MD = 6.22, 95% CI (4.12, 8.32), p < 0.00001], and BI levels rose [MD = 4.95, 95% CI (2.96, 6.93), p < 0.00001]. In conclusion, traditional Chinese exercises offer significant benefits in treating PSD, demonstrating both efficacy and safety.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/view/CRD42024574791.